#largeculturalinsitutionsinpandemic #philharmonichallstheatresmuseumsintheinternet (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
Author presents the activity of selected Polish large cultural institutions – theatres, museums, philharmonic halls – during COVID-19 pandemic with particular reference to the changes in their offer and internet activity. The internet activity of chosen institutions and media statements of their representatives were analyzed. On that basis the specificity of art popularization during lockdown was presented. The hierarchy of the functions of art and basic aims of such institutions have been modified. The experience of cultural participation is being modified by the specificity of mediated activity in the Web. This situation is symptomatic of the crisis which subsequent stages have fluid dynamics. In the “new orientation” stage certain advantages might be worked out in spite of complicated situation. The article presents the analysis of restrictions and non-obvious potential of the situation, both from the perspective of the institutions and participants of cultural life. The SWOT matrix was used to present the conclusions.